En rig kvindegrav med hesteudstyr - nye resultater fra Tombølgård - Jensen, Mads Leen (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
In 2018, the Museum Sønderjylland carried out an excavation of the cemetery site of Tombølgård on the island of Als, southern Jutland, which has been partly destroyed by modern ploughing. The cemetery site dates to the Early Roman Iron Age, B 1 and B 2. The site is known from a small excavation of a single urn in 1932, and from metal detector finds found between 2016 and 2018. During the excavation in 2018, the last four cremation graves, of which two were intact, were excavated. This article presents the grave goods from one of these two cremation graves. It included a gold berlock pendant, a Roman saucepan, a bridle, and horse headgear. The bridle and headgear belong to the earliest Germanic types, and parallels may be drawn to the Rhine area and the auxiliary cavalry units posted there during the Roman expansion of the area up to the Elbe.